Analisis Pengalaman Nasabah dalam Menghadapi Permasalahan pada Bank Rakyat Indonesia (BRI) dan Bank Mandiri di Kota Sungai Penuh - Wahyu Fikri; Zul Ihsan Mu’arrif (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to explore customers' experiences in resolving banking issues. The approach used is qualitative research, focusing on gaining an in-depth understanding of the experiences of customers of Bank Rakyat Indonesia (BRI) and Bank Mandiri in Kota Sungai Penuh. The data analysis technique applied is Domain Analysis, which emphasizes general descriptions and a comprehensive understanding of the subject or social group being studied. Primary data collection was conducted through semi-structured interviews with customers. Additionally, secondary data was gathered from previous literature studies. Moreover, trust has been proven to play a significant role in enhancing customer satisfaction. This study suggests that banks should improve service quality and consider customer feedback to build better relationships.